EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN MONOAKSI TERHADAP INTERAKSI SOSIAL PESERTA DIDIK KELAS IV DALAM PEMBELAJARAN TEMATIK - Umi Habibah; Lukman Nulhakim; Ana Nurhasanah (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2023)
This study aims to determine the efectiviti of the use of monoaxic learning media on the social interaction of grade 4 students in thematic learning. The research method used is Quasi Experiment, this study uses two classes, the control class and the experimental class. Class 4 A is the control class with 28 students and class B is the experimental class with 28 students. This research was conducted from August 2021 to October 2022 located at SDN 09 Serang City. Based on the research that has been done, it shows that there is high effectiveness from the use of monoaxic learning media for students' social interactions. This can be seen from the results of student questionnaire data calculations using monoaxis learning media is 80,7 while student questionnaire calculations using image learning media are 56 .based on the results of the t test which obtained results 0,00 < 0,05 then it can be it can be concluded that the use of monoaxic learning media for interactions has effectiveness. As well as when compared to the use of monoaxic learning media it is better than image learning media.